Heart Failure-Smart Life: a randomized controlled trial of a mobile app for self-management in patients with heart failure - Choi, Eui Young; Park, Jin Sun; Min, Deulle; Ahn, Soohyun; Ahn, Jeong Ah (BMC Cardiovascular Disorders, 2023)
Background: It is an important strategy for healthcare providers to support heart failure patients with comprehensive aspects of self-management. A practical alternative to a comprehensive and user-friendly self-management program for heart failure patients is needed. This study aimed to develop a mobile self-management app program for patients with heart failure and to identify the impact of the program. Methods: We developed a mobile app, called Heart Failure-Smart Life. The app was to provide educational materials using a daily health check-up diary, Q & A, and 1:1 chat, considering individual users’ convenience. An experimental study was employed using a randomized controlled trial to evaluate the effects of the program in patients with heart failure from July 2018 to June 2019. The experimental group (n = 36) participated in using the mobile app that provided feedback on their self-management and allowed monitoring of their daily health status by cardiac nurses for 3 months, and the control group (n = 38) continued to undergo their usual care. The differences in the physical, psychosocial, and behavioral factors between the two groups over time were analyzed using the analysis of covariance. Results: After 3 months of intervention, significant differences between experimental and control groups were shown in the New York Heart Association functional class (p = 0.003) and cardiac diastolic function (p = 0.024). The improvements over time in the experimental group tended to be higher than those in the control group in considered variables. However, no changes in psychosocial and behavioral variables were observed between the groups over time. Conclusions: This study provides evidence that the mobile app program may provide benefits to its users, specifically improvements of symptom and cardiac diastolic function in patients with heart failure. Healthcare providers can effectively and practically guide and support patients with heart failure using comprehensive and convenient self-management tools such as smartphone apps.
Keywords: Heart Failure; Humans; Mobile Applications; Self-Management; Heart failure; Mobile applications; Self-management; Telemedicine